(untitled) (Ameghiniana, 2014)
A rapid increase of water depth associated with dysoxic bottom conditions took place in the central part of the Precordillera basin during the middle Darriwilian. The peak of transgression and drowning of the carbonate ramp are marked by the transition from the uppermost carbonate beds of the San Juan Formation to a rhythmic alternation of graptolitic black shales and marlstones (base of the Los Azules Formation). This lithofacial change is associated to a drastic faunal shift involving a renewal of the ecologic structure. The carbonate facies dominated by filter-feeding organisms were rapidly replaced by new communities characterized by benthic and pelagic trilobites and low-richness assemblages of minute brachiopods. Two main associations are recognized in the Los Azules Formation: a basal ephemeral Sivorthis-Mendolaspis Association and a more persistent Chilcorthis-Palaeoglossa Association inhabiting deeper and more dysoxic sea-bottoms. The new plectorthoid family Chilcorthidae is established to include the new genus Chilcorthis. Five new species are described: Palaeoglossa minima sp. nov., Cyrtonotreta vasculata sp. nov., Philhedra pauciradiata sp. nov., Sivorthis precordillerana sp. nov., and Bockelia canalis sp. nov. Associate taxa are Anomaloglossa? sp., Cyrtonotreta? sp., Protohesperonomia? sp., Syntrophia? sp. and unidentified Finkelnburgiidae, Polytoechiidae and Aegiromenidae. The first successful deep-water incursions are Floian–Dapingian in age, but from the Darriwilian they have been documented in several paleoplates. These pre-Sandbian brachiopod communities were more restricted geographically than the global Foliomena Fauna with which they share some taxa and similar morphotypes but differ in the higher proportion of linguliform brachiopods and less diverse plectambonitoids.